(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This article is concerned with the concepts of weakly θ b(Λ,p)-open functions and weakly θ b(Λ,p)-closed functions. Moreover, some characterizations of weakly θ b(Λ,p)-open functions and weakly θ b(Λ,p)-closed functions are established.